PENTINGNYA DIGITAL MARKETING DALAM MENAIKKAN PENJUALAN PERUSAHAAN - Putra, Ali Syah (Jurnal Mahkota Bisnis (Makbis), 2024)
With the rapid growth of the internet and the increasing demand for digital content, digital marketing strategies have become increasingly crucial for modern businesses. These strategies leverage various platforms and digital tools to engage and communicate with target audiences, enhance brand awareness, drive sales growth, and strengthen customer engagement. While digital marketing presents numerous opportunities, businesses also face challenges such as building brand recognition, overcoming sales obstacles, and improving customer interaction. This paper comprehensively examines the impact of digital marketing strategies on brand awareness, sales growth, and customer engagement. The research employs both quantitative and qualitative approaches, combining empirical data with case study analysis. Additionally, this study explores the role of various platforms and digital tools in brand promotion and evaluates the influence of personalized marketing and interactive activities on increasing sales and customer engagement.